A Late Bronze Age II clay coffin from Tel Shaddud in the Central Jezreel Valley, Israel: context and historical implications. (4th May 2017) - van den Brink, Edwin C. M.; Beeri, Ron; Kirzner, Dan; Bron, Enno; Cohen-Weinberger, Anat; Kamaisky, Elisheva; Gonen, Tamar; Gershuny, Lilly; Nagar, Yossi; Ben-Tor, Daphna; Sukenik, Naama; Shamir, Orit; et al.
Abstract : To the memory of Trude Dothan 1922–2016 During trial excavations carried out in 2013 on behalf of the Israel Antiquities Authority, a seemingly isolated clay coffin with anthropoid lid, containing a single primary burial, was uncovered within a 6 m × 5 m probe bordering the lower east slope of Tel Shaddud in the Jezreel Valley. It lay at the bottom of a tightly constricted burial pit, about 1.8 m below the present surface. Subsequent salvage excavations in 2014 uncovered, less than 3 m to its south-east, a further three burial pits (none of which contained a coffin), enclosing four additional primary burials, oriented east to west — in conformity with the coffin burial. Together these burials form part of an apparent Late Bronze Age II–Iron Age I burial ground at the eastern margin of Tel Shaddud. The coffin and associated funerary gifts bear a strong resemblance to comparable specimens and associated funerary assemblages known foremost from Deir el-Balah in the Gaza strip and Bet Sheʽan in the Jordan Valley. The shared mortuary aspects of Tel Shaddud and the latter sites indicate a strong link with New Kingdom Egypt. Based on the Tel Shaddud data and its very location, in combination with selective reading of relevant, near-contemporary historic records (i.e. the el-Amarna letters) it is argued here that Tel Shaddud was a way station, or estate, functioning within the framework of the Egyptian New Kingdom colonization of the region during the Late Bronze Age II and succeeding Iron Age I.